CALIFORNIA LOCAL UPDATE - MCADAM, B (Tufts Archival Research Center, 2007)
Memorandum from Bob McAdam to the State Activities Policy Committee regarding the actions on a local level in California of several cities and towns regarding tobacco and smoking regulations.